OPTIMALISASI LITERASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AS-SALAM MALANG - Ach. Faiq Maulana; Maskuri Maskuri; Bahroin Budiya (VICRATINA, 2022)
This article will try to describe the School Literacy Movement, in the context of Islamic educational learning as well as the literacy movement is an important aspect, the school literacy movement is an inherent part of learning Islamic religious education.  The objectives of this study are: To describe the planning for literacy optimization in learning Islamic religious education at the As-Salam Integrated Islamic Junior High School, Malang City;  To explain the implementation of literacy optimization in learning Islamic religious education at the As-Salam Integrated Islamic Junior High School, Malang City; To describe the results and evaluate the optimization of literacy in the learning of Islamic religious education at the As-Salam Integrated Islamic Junior High School Malang. The results showed that: 1) literacy planning in schools is shown by the school's attention to aspects of physical and non-physical facilities, while in the context of learning the same is carried out based on the principles of literacy media and literacy learning media; 2) in its implementation, literacy awareness is reflected through three classifications, namely habituation, development and learning; 3) The results show that the optimization of literacy has implications for the critical thinking ability of students and their ability to apply the principle of screening (curation) in literacy information, evaluation is seen based on the space of expression of literacy achievement which is still small and needs to be redeveloped.